Connecting the dots between human malaria, livestock, and under-nutrition: An unexpected pathway. - Griffiths, Jeffrey. (Tufts University. Tisch Library., 2017)
This presentation uses new data to link malaria outcomes with livestock ownership- particularly cows.; Keywords: Uganda, malaria, livestock, nutrition, agriculture, malnutrition, Tufts University.; NIL Presentations 2013-2015.; Feed the Future Innovation Lab for Nutrition, USAID Contract No. AID-OAA-L-10-000006, managed by Tufts University's Gerald J. & Dorothy R. Friedman School of Nutrition Science and Policy